Influences of initiator addition methods in suspension polymerization of vinyl chloride on poly(vinyl chloride) particles properties. Issue 2 (6th January 2016) - Bijhanmanesh, Mohammad Javad; Etesami, Nasrin; Esfahany, Mohsen Nasr
Abstract : Vinyl chloride suspension polymerization was carried out in a pilot‐scale reactor to study the effects of different methods of initiator addition on poly(vinyl chloride) (PVC) resin properties. The experiments used different arrangements for adding the initiator to the reactor, whereas other reaction conditions were the same: (i) initiator was added to the continuous aqueous phase and then monomer was dispersed in it (conventional method); (ii) initiator was predissolved in monomer before dispersing in the continuous aqueous phase; and (iii) suspending agents along with initiator were added to the monomer before polymerization. The PVC resin prepared by method of (i) had a higher monomer conversion and a higher Sauter mean diameter of grains with a narrow particle size distribution comparable to that of PVC resins by other methods. Scanning electron microscopy showed more uniform particles and fused primary particles in the grains, which confirms lower porosity and lower cold plasticizer absorption (CPA) for PVC grains produced by procedure of (ii). The results showed that when the suspending agents were also predispersed in monomer along with initiator (iii), CPA increases dramatically due to internal porosity of the grains. Simultaneously, a marked decrease in Sauter mean diameter was apparent. Scanning electron microscopy micrographs show that primary particles in the interior of PVC grains prepared by the latter method are looser, and there is more free volume between primary particles resulting the high internal porosity and consequently higher CPA. Mercury porosimetry analysis also confirms these results. K value as a molecular weight characteristic for all methods was the same . J. VINYL ADDIT. TECHNOL., 24:116–123, 2018. © 2016 Society of Plastics Engineers